Naming System on The Name of Banten Batik Motif: A Semantic Study - Sari, Nur Amalina; Nurhayati (Development in Language Studies, 2022)
Semantics studies involve investigating the meaning of language, including one that examines the naming system of people’s names, animal names, place names, and object names. In this study, semantics analysis is used to explore the naming of Batik motif names of Banten. The article aims to study are (1) to classify the factors that influence the naming system of the name of Banten batik motives, and (2) to describe the naming system of the Banten batik motives based on semantics study. In addition, this study has used the descriptive qualitative technique. Then, the survey and the library method with analyzing the variety of sources of text and/or written documents are utilized to collect data. The findings revealed that six categories of factors influence the naming of Banten batik names based on: (1) the name of nobility in Banten, (2) the toponym name of an ancient village or village in the Banten region, (3) the name of building construction, (4) the name of the place in the form of spatial (indoor) in the Sultanate of Banten, (5) the name of function places in the outdoors, and the last is (6) the name of natural phenomena.